First record of Pinnularia subinterrupta Krammer & Schroeter in Poland – a rare species in Europe - Noga, Teresa; Rybak, Mateusz (Biodiversity: Research and Conservation, 2017)
The first record of occurrence of Pinnularia subinterrupta Krammer & Schroeter in Poland with the species ecological and morphological characteristics (including scanning electron microscope details) are provided. The species was observed in the material collected from the Jamów and Tokarka streams, flowing from the areas of raised bog in the Orava Region of southern Poland. Pinnularia subinterrupta occurred in low abundance, among mosses, and always at low water pH (3.3-4.8), conductivity (28-63 mS cm-1) and temperature (3.9-9.6°C).